Outcomes of Patients Treated with the Everolimus- versus the Paclitaxel-Eluting Stents in a Consecutive Cohort of Patients at a Tertiary Medical Center - Shammas, Nicolas W.; Shammas, Gail A.; Nader, Elie; Jerin, Michael; Mrad, Luay; Ehrecke, Nicholas; Shammas, Waheeb J.; Voelliger, Cara M.; Hafez, Alexander; Kelly, Ryan; Reynolds, Emily (International Journal of Angiology, 2013)
In this study, we compare the outcomes of the paclitaxel-eluting stent (PES) versus the everolimus-eluting stent (EES) treated patients at a tertiary medical center and up to 2 years follow-up. Unselected consecutive patients were retrospectively recruited following stenting with PES (159 patients) or EES (189 patients). The primary endpoint of the study was target lesion failure (TLF), defined as the combined endpoint of cardiac death, nonfatal myocardial infarction (MI), or target lesion revascularization (TLR). Secondary endpoints included target vessel revascularization (TVR), TLR, target vessel failure (TVF), acute stent thrombosis (ST), total death, cardiac death, and nonfatal MI. Patients treated with the PES stent had less congestive heart failure and restenotic lesions, but a higher prevalence of longer lesions, nonleft main bifurcations, required more stents per patient (4.3 ± 2.8 vs. 2.9 ± 2.1). TLF occurred in 32.3% PES versus 21.5% EES (p = 0.027). The secondary unadjusted endpoints for PES versus EES, respectively, were TVF 38.6 versus 30.7% (p = 0.140), TVR 35.7 versus 26.5% (p = 0.079), definite and probable ST 1.2 versus 0.0%, nonfatal MI 4.5 versus 4.2%, and mortality 9.6 versus 4.0%. Logistic regression analysis showed that the numbers of stents per patient (p = 0.001), age (p = 0.01), and renal failure (p = 0.045) were independent predictors of TLF. Using univariate analysis, EES had lower TLF than PES in a cohort of unselected patients undergoing percutaneous coronary intervention at 2 years follow-up. Multivariate analysis showed that the numbers of stents per patient, age, and renal failure, but not stent type, were predictors of TLF.
Keywords: coronary stent; drug-eluting stent; paclitaxel; everolimus; outcome; target lesion revascularization; stent thrombosis